Instrumental Studies in Arabic Phonetics. - Hassan, Zeki Majeed (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2011)
Brought together in this volume are fourteen studies using a range of modern instrumental methods - acoustic and articulatory - to investigate the phonetics of several North African and Middle Eastern varieties of Arabic. Topics covered include syllable structure, quantity, assimilation, guttural and emphatic consonants and their pharyngeal and laryngeal mechanisms, intonation, and language acquisition. In addition to presenting new data and new descriptions and interpretations, a key aim of the volume is to demonstrate the depth of objective analysis that instrumental methods can enable resea.